2017
DOI: 10.1038/cddis.2017.441
|View full text |Cite
|
Sign up to set email alerts
|

Blocking autophagy enhances the apoptotic effect of 18β-glycyrrhetinic acid on human sarcoma cells via endoplasmic reticulum stress and JNK activation

Abstract: Sarcoma, a rare form of cancer, is unlike the much more common carcinomas as it occurs in a distinct type of tissue. The potent antitumor effects of 18β-glycyrrhetinic acid (GA), a novel naturally derived agent, have been demonstrated in various cancers. However, the effect of GA on human sarcoma, and the underlying mechanisms, remain to be elucidated. In the current study, we show that GA inhibits sarcoma cell proliferation by inducing G0/G1-phase arrest. Exposure to GA resulted in the activation of caspase-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 44 publications
4
23
0
Order By: Relevance
“…Existing evidence demonstrated that ER stress plays a vital role in the induction of apoptosis and autophagy in various tumor cells, including melanoma cells [31], sarcoma cells [32], glioblastoma cells, gastric cancer cells [38], and liver cancer cells [39]. In this study, we found that XAG treatment induced apoptosis and ER stress mediated autophagy in Bel 7402 and SMMC 7721 cells.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Existing evidence demonstrated that ER stress plays a vital role in the induction of apoptosis and autophagy in various tumor cells, including melanoma cells [31], sarcoma cells [32], glioblastoma cells, gastric cancer cells [38], and liver cancer cells [39]. In this study, we found that XAG treatment induced apoptosis and ER stress mediated autophagy in Bel 7402 and SMMC 7721 cells.…”
Section: Discussionsupporting
confidence: 55%
“…A more recent evidence emphasized that JNK/c-jun pathway was involved in ER stress-mediated autophagy [32]. Thus, we attempted to investigate whether XAG-induced ER stress mediating autophagy through activation of JNK pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the induction of ER stress by chemotherapeutic drug could further promote cell death by various mechanisms in cancer cells [17,18]. Considering that ER stress plays a crucial role in the regulation of cell death, as well as programmed necrosis [19,20], we speculated that PRIS might induce ER stress-mediated cell death in lung cancer.…”
Section: Introductionmentioning
confidence: 96%
“…Accumulating evidence suggests that autophagy can both suppress and promote tumor functions in cancer progression [6,7]. On the one hand, the initial stages of tumorigenesis can be inhibited by autophagy [8] and on the other, autophagy could nurture established cancers [9][10][11]. Yang et al [12] revealed the mechanism of how autophagy promotes pancreatic tumor growth via p53 alternation.…”
Section: Introductionmentioning
confidence: 99%